PENGARUH KUALITAS PELAYANAN DAN BEBAN KERJA PRAMUKAMAR TERHADAP KEPUASAN TAMU YANG MENGINAP DI HOTEL INNA PARAPAT - RIANTO MANURUNG (JURNAL ILMIAH KOHESI, 2020)
This research aims to test the influence of quality of service and workload on the quality of service Hotel Inna Parapat. Thetype of research used is quantitative research. The study used the census method with the questionnaire instrument, thesampling technique in the study using probability sampling technique using total sampling, so that the sample was 75 people.Processing techniques and data analysis using validity tests, reliability tests, classical assumption tests, descriptive analysis,cross tabulation, multiple linear regression analyses, and coefficient of determination analysis. The results showed thatindividually the quality of service significantly affects the guest's satisfaction and the workload is significant and is a dominantvariable towards guest satisfaction. The results of the test are jointly quality of service and workload significantly affect theguest satisfaction of Hotel Inna Parpaat. The value of RSquare is 0.719 or 71.90%, which means that the research variablesgive contribution or contributions very large in explaining about the quality of service Inna Parapat Hotel for 71.90% while therest is 28.10% influenced by other factors outside this research.